Palonosetron for the treatment of chemotherapy-induced nausea and vomiting. (December 2014) - Navari, Rudolph M
<x xml:space="preserve">Abstract</x> Introduction: Chemotherapy-induced nausea and vomiting (CINV) is associated with a significant deterioration in quality of life. The emetogenicity of the chemotherapeutic agents, repeated chemotherapy cycles, and patient risk factors significantly influence CINV. The introduction of 5-hydroxytryptamine-3 (5-HT3) receptor antagonists has been a major factor in the improvement of the prevention of chemotherapy-induced acute and delayed emesis. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Palonosetron&logicalOpe1=OR&field2=articletitle&text2=Palonosetron&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Palonosetron, a second-generation 5-HT3 receptor antagonist with a different half-life, a different binding capacity, and a different mechanism of action than the first-generation 5-HT3 receptor antagonists appears to be the most effective agent in this drug class. Areas covered: Palonosetron's chemistry, pharmacodynamics, pharmacokinetics, metabolism, clinical efficacy, including comparison with other antiemetics, role in controlling nausea, potential role in multi-day chemotherapy and bone marrow transplantation, and overall safety are discussed. Expert opinion: The clinical data in the literature have established palonosetron as the 5-HT3 receptor antagonist of choice in terms of efficacy and safety for the prevention of CINV for patients receiving moderately or highly emetogenic chemotherapy. Three international guidelines have listed palonosetron as the preferred 5-HT3 receptor antagonist. Due to its higher efficacy, the use of palonosetron may be more cost effective compared to the generic first-generation 5-HT3 receptor antagonists. Clinical organizations' pharmacy and formulary committees should consider efficacy when making recommendations for agents for the prevention of CINV.